The porcine carotid body: morphological and lectin histochemical characterization - Semzenisi, Ecaterina; Ungur, Andrei; Feher, Mihai-Cristian; Hoţa, Alexia-Teodora; Hodor, Dragoṣ; Pop, Romelia; Tăbăran, Alexandru-Flaviu (Frontiers in Veterinary Science, 2026)
Although the carotid body (CB) has been widely examined in many animal species, its histological features in pigs have received comparatively little attention. This research presents the first integrative description of the porcine (CB), combining anatomical dissection, histological evaluation (H&E and Masson's trichrome), immunohistochemistry, and lectin histochemistry. In the study, four piglets were examined from which the carotid glomus was harvested, and it was described histologically. The organ displayed a multilobular structure embedded in connective tissue. Immunohistochemical labeling with GFAP, S100, and NSE demonstrated strong and consistent immunoreactivity, confirming the presence of neuroendocrine and glial-like cell populations. Complementary lectin histochemistry with Con-A and WGA revealed distinct glycosylation patterns that correlate with the presence of growth factor receptors (TrkA, TrkB, TrkC, p75NTR, and others), thereby offering insight into receptor biology and glycan-mediated signaling within the (CB).